(3CfHGA GdRef aj JGQjN Gdjefs - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO, GHf GdbGpSe,J (B1099 (3g` s
(3ChdgG (B:s
(3GdMeO ddg (B,(3HYO aEf GdJGQjN deG cGf eYQaJg ef LedI GdYdhe GdOjfjI hajg GdZhGW GdJi djSJ NGaJI Ydi Phi GdCMdGe GdPcjI , abO bU GdJYGdi bUU GdeGVjf ai cJGHg GdcQje s
(3BNQgG (B:s
(3BNQg ef MhGOK SfI JSY hJSYjf hSJeGjI bhdg (B: (3Ke aJMhG GdTGe heUQ hGdYQGb ceG SjCJi PcQg hEdi gPG GdehVg GfJgi GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3HChdgG bQGAI ef eMeO Hf YHO Gddg Hf GdMSjf Hf CejQ GdeDefjf SfI (B1098 (3Ydi MhGTjgG JYdjbGJs
(3GdfSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B192s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs